Epilepsy and Hippocampal Injury - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The relationship between hippocampal cell loss and mossy fiber sprouting (MFS), and the occurrence of spontaneous seizures (epilepsy) following early-life status epilepticus was investigated in laboratory studies at the Division of Neurology, Children's Hospital of Philadelphia and University of Pennsylvania School of Medicine, Philadelphia, PA.